Enterprises’ initiatives intended for persons aged 50 and over in the Opole Special Demographic Zone - Jastrzębska, Ewa (Research Papers of Wrocław University of Economics, 2018)
Adverse demographic changes (ageing of the population, negative population change, depopulation) and their negative effects are currently among the key barriers to development, not only in developed countries. Particularly affected by such challenges, in 2014 the Opole region (admin. Opolskie Voivodeship, Pol. województwo opolskie) launched a Special Demographic Zone (SDZ) programme covering the entire administrative area. One of the four thematic packages of the programme is addressed to people aged 50+ and entrepreneurs are among the key programme implementing partners. This article aims to assess the initiatives created for seniors by selected enterprises seated in the SDZ; the assessment is based on conducted surveys
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 81-90
Keywords: demographic change; ageing of the population; Opole Voivodeship; seniors; specialdemographic zone; enterprises; zmiany demograficzne; starzenie się społeczeństw; województwo opolskie; osoby starsze; specjalna strefa demograficzna; przedsiębiorstwa